2D ECHO Study to Correlate Anthropometric Parameters and Dimensions of Semilunar Valves in Population of Telangana, India - Sandhya Rani Chatripalli; Jana Siva Koti Srinivasa Rao (International Journal of Anatomy Radiology and Surgery, 2022)
Introduction: Measurement of the aortic and pulmonary valve dimensions is critical in diagnosing stenotic diseases as well as preparation of prosthetic valves. A study of these valve dimensions in a normal population as well as comparing it with the built of a person could give us more insight to help prepare better prostheses and achieve better results after valve replacement procedures.